Integrating phonological and phonetic aspects of Mandarin Tone 3 sandhi in auditory sentence disambiguation - Lai, Wei; Li, Aini (Laboratory phonology, 2022)
This study investigates whether Mandarin listeners integrate a prosody-covarying phonological variable, the Chinese Tone 3 sandhi (T3S), into auditory sentence disambiguation. The T3S process changes the first of two consecutive low tones (T3) into a rising tone. It applies obligatorily within a foot and optionally across feet. When T3S is optional, it is more likely to apply to Tone 3 syllables across smaller prosodic boundaries than larger ones; the smaller the boundary, the sharper the T3S pitch rise. Participants listened to twenty-seven structurally ambiguous sentences and identified from two written interpretations the one consistent with what they heard. Each sentence contains two consecutive Tone 3 syllables, and posing different prosodic boundaries between the Tone 3 syllables would result in different interpretations. The first Tone 3 syllable was manipulated into three tone shapes (sharp-rising, shallow-rising, low) and two duration types (long, short). The results show higher major-juncture interpretation rates when the first Tone 3 is long than short, when T3S does not apply than when it applies, and when T3S has a shallower than sharper pitch slope. The tone effect further interacts with the foot formation of Tone 3 syllables in each sentence. We propose that listeners have sophisticated knowledge of prosodic variables and use it efficiently in linguistically meaningful contexts.